Synthesis, spectral analysis and in vitro cytotoxicity of diorganotin (IV) complexes derived from indole‐3‐butyric hydrazide. (28th May 2020) - Devi, Jai; Yadav, Jyoti; Kumar, Deepak; Jindal, Deepak Kumar; Basu, Biswarup
Abstract : A series (1–20 ) of diorganotin (IV) complexes with general formula R2 SnL were formed by the reaction of R2 SnCl2 (where R = Me, Et, Bu and Ph) with Schiff base ligands (H 2 L 1–4 ) derived from the reaction of indole‐3‐butyric hydrazide with the salicylaldehyde and its derivatives. The structure elucidation of compounds were done by using UV–Vis, FT‐IR, NMR ( 1 H, 13 C, 119 Sn), Mass spectrometry and thermal gravimetric analysis. Spectroscopic evidences suggested tridentate nature (ONO) of Schiff base ligands and coordinated to the dialkyl/diaryltin (IV) moieties through nitrogen and oxygen donor sites giving pentacoordinated geometry to complexes. The compounds were tested for the antimicrobial activity against bacterial and fungal strains which showed promising biological activity with compound 20 (Ph2 SnL 4 ) as most active against microbes. The in silico study of the compounds was carried and observed that the compounds are used as orally active drugs and promote the formation of different hydrazide based drugs. The synthesized compounds were tested against human carcinoma cell lines namely A549, MCF7 and one normal cell line IMR 90 using MTT assay. The diethyl and dibutyltin complexes of Schiff bases displayed good cytotoxic activities. Compound 3 (H2 L 3 ) and 10 (Et2 SnL 2 ) were most potent against cancer cell lines with lowest IC50 values and 7–8 times less toxic against the normal cell line. Abstract : A series (1–20) of diorganotin (IV) complexes were synthesized with tridentate (ONO) hydrazide Schiff base ligands. Compounds exhibited good biological activities with complexes 10 and 20 as most potent candidates for anticancer and antimicrobial activities.